O sexto eixo da PNAISH: a inclusão da saúde mental como parte fundamental da política de saúde do homem - Turri, Geovanna Santana de Souza (2024)
In Brazil, men's health care is guided by the National Policy for Comprehensive Men's Health Care (PNAISH), which was established with the aim of improving the health conditions of this population. PNAISH comprises five guiding principles: a) access and reception, b) sexual and reproductive health, c) fatherhood and caregiving, d) prevalent diseases in the male population, and e) prevention of violence and accidents. For the Ministry of Health, these principles are essential to address the male population's needs, considering the relevance of these topics. Nevertheless, it is noteworthy to mention an existing gap within these principles, as specific aspects related to men's mental health have not been highlighted. PNAISH, thus far, does not effectively address the emotional and psychological dimensions that are related to the comprehensive health of the male population. In this thesis, we considered the inclusion of mental health as a guiding principle of the PNAISH as extremely relevant in the Brazilian context. The primary objective of this proposal was to advocate for the inclusion of a sixth guiding principle for the PNAISH – mental health – based on a comprehensive review of the literature, highlighting the significance of male mental health within the framework of comprehensive healthcare. We conducted three studies to support the formulation of legislation aimed at the inclusion of mental health as an essential guiding principle of the PNAISH. The first study aimed to perform a theoretical-reflexive discussion regarding PNAISH and men's mental health, advocating for its inclusion based on scientific articles and official documents. The second study performed empirical research aiming to identify men's perceptions during the COVID-19 pandemic, categorizing them into groups based on the absence or presence of depressive and anxious symptoms. The third study aimed to analyze correlations between depression and anxiety symptoms in men, focusing on identifying the strongest correlations between these variables. The results of the three studies informed the creation of the proposed legislation, which aims to amend and complement the PNAISH by adding mental health as the sixth guiding principle, presented at the end of this thesis. In conclusion, we considered that the proposed objectives were achieved and that these findings will guide new mental health interventions within PNAISH, making it more effective in providing comprehensive healthcare for men.